Effect of intense wrestling exercise on leucocytes and adhesion molecules in adolescent boys - Nemet, D.; Mills, P. J.; Cooper, D. M. (British Journal of Sports Medicine, 2004)
Background: In adults, exercise is a powerful and natural stimulator of immune cells and adhesion molecules. Far less is known about exercise responses during childhood and adolescence and whether or not exercise in "real life" activities of healthy adolescents influences immune responses.